Traditional Ethno-Medicinal Plants Used for the Treatment of Diabetes in Radhapuram Taluk, Tirunelveli District, Tamilnadu, India - Ramarajan, Sekar; Murugesan, A. G.; Saravana Ganthi, A. (Indian Forester, 2017)
The present study deals with the documentation of 37 species of medicinal plants used for the treatment of Diabetes problems. Anti-diabetic plants are used either in single or in combination with some other plant parts. The study of indigenous medicine as a therapeutic agent has its importance in addressing health problems of village communities. Conclusion: Further, indigenous medical approach for the treatment of diabetes is a practical, cost-effective and biologically safe. Anti-diabetic medicinal plants used in Radhapuram Taluk, Tirunelveli district have been listed along with plant parts used and life form.